INFORMATION SYSTEMS FOR EFFECTIVE EDUCATIONAL INSTITUTION MANAGEMENT - SHVARDAK, Marianna (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2025)
The article addresses the pressing issue of using information systems as a key tool for organizing and supporting management processes in general secondary education institutions. It presents an overview of the theoretical foundations of information system functionality in the educational field, highlighting their main advantages and functional purposes in the context of digitalization. Particular attention is paid to the capabilities of digital technologies in data storage and processing, administrative activity optimization, increased transparency, and providing open access to information for all participants in the educational process. The aim of the article is to characterize the information systems applied in the educational sphere and analyze their significance for the organization and support of management processes in educational institutions. The article provides an analysis of modern information systems implemented in domestic educational practice, including AIKOM2, ISUO, EDEBO, EvaluEd, among others. Their functional capabilities are revealed, particularly in data collection, processing and analysis related to staffing, the educational process, financial reporting, document management, and tools for monitoring the quality of education. These systems are identified as providing analytical support for decision-making, integrating the activities of various institutional departments, and enhancing management effectiveness. The article emphasizes that the implementation of such systems is a significant step toward creating an effective digital education management ecosystem. It highlights the potential of information systems to improve strategic planning mechanisms, increase the quality of management decisions, and enable responsive adaptation to changes in the internal and external environment of educational institutions. It is noted that the use of information systems enables the formation of a unified information space that supports communication among all participants in the educational process–administration, teachers, students, parents, and education authorities. The need for further research into the functional characteristics of educational IT solutions is stressed, aiming to refine educational management models in the context of digital transformation. Effective implementation of management information systems promotes the development of open, flexible, and result-oriented governance in educational institutions, ensuring improved quality of managerial decisions, strategic planning, and internal control.